How is the siida going to continue? - Sara, Mikkel Nils (Sámi dieđalaš áigečála, 2026)
The siida (plural: siiddat) is of both ancient and contemporary interest. Siiddat were and re main local Sami communities, which thanks to written sources, we know met and negotiated  with trades people and representatives of neighbouring and southern powers centuries ago. The siida even predates these written sources. Nowadays siiddat primarily organize the day-to-day practices of reindeer herding and siiddat have undergone major changes primarily due to the growing influence from outside.The main features of this institutions continuity are the existence of siida territories, the membership of Sami families in the siida through generations, the membership also of their animals, and traditional Sami knowledge. Reindeer, or rather in Sami, boazu, has at all times been a member of the siida. Reindeer constituted a minor part of the siida in earlier times, but have been growing in importance over the last three or four centuries. The relations between reindeer as boazu and the Sami reindeer herder is used as an example to demonstrate elements of the traditional knowledge of reindeer herding Sami and their worldview. The reindeer herding Sami way of thinking stands for a day-to-day relation to questions of sustainability and ethics, which I term ‘a siida way of thinking’, as opposed to the economic and ecological modelling encountered in official and administrative thinking and direction.A focus needs to be placed on a clarification of siida land rights, moreover on a protection and realization of the siida right to selfdetermination in internal affairs, thereby acknowledging the importance and relevance of traditional Sami knowledge. This is decisive for the continuation of the Sami siida system.